Use of pulsed electric field to extract rapeseed oil and investigation of the qualitative properties of oils. (11th August 2022) - Mazroei Seydani, Lida; Gharachorloo, Maryam; Asadi, Gholamhassan
Abstract: Rapeseed is one of the most commercially important oil crops in the world due to its high amount of oil stored in seeds and high nutritional value. In this study, the pulsed electric field (PEF) was used as a nonthermal pretreatment before extraction of rapeseed oil to increase extraction efficiency and improve the quality characteristics of rapeseed oil. Four levels of electric field intensity (0, 1, 4, and 7 kV/cm) with 30 and 80 pulse numbers and pulse width of 20 μs were applied and after treatment the samples were transferred to a cold press machine for oil extraction. Oil extraction efficiency, chlorophyll and carotenoid contents, fatty acids profile, oxidative stability, total phenolic content, peroxide, and acid values of extracted oil were determined. The results indicated that an increase in the electric field intensity and pulse number, total phenolic compounds and oxidative stability of rapeseed oil increased compared to the control ( p  < .05). Treating at 4 kV/cm and 80 pulse numbers was obtained as the highest extraction efficiency (46.11%), while with the further increase of the electric field intensity, the efficiency of the oil extraction process decreased (the extraction efficiency at 7 kV/cm and 80 pulse numbers was 45.94%). The highest phenolic compounds (320.04 ppm) and energy input (31.36 kJ/kg) were related to the intensity of 7 kV/cm and 80 pulse numbers. This study showed that the use of PEF is a suitable method for rapeseed pretreatment with no detrimental effects on extracted rapeseed oil quality. Practical Applications: In recent years, new technologies such as PEF have been used in oil extraction due to their positive effects. The selection of nonthermal technologies to reduce process time, energy consumption, and economic issues as an industrial goal to improve food quality has been considered. The technology proposed in this study shows, that applying PEF for treating the rapeseed before oil extraction should be presented as an appropriate pretreatment in oil extraction industries. The PEF also showed a suitable impact on the quality of the rapeseed characterized. Abstract :